The Mediation Role of Mushroom Management in the Effect of Organizational Trust on Intention to Leave in Sports Businesses - Bozkir, Akif; Şakar, Murat (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The management style and understanding in sports businesses have a significant effect on the employees’ sense of trust in the organization and their intention to leave. The aim of this research is to determine the mediating role of mushroom management in the effect of organizational trust on turnover intention. Aim: The purpose of this research is to determine the role of mushroom management as an mediating in the effect of organizational trust on the intention of leaving. Method: The research data were obtained by applying face-to-face survey method to sports business employees voluntarily during the pandemic period. The data obtained were analyzed using SPSS 23.0, Amos and IBM SPSS Process Macro package programs. Results: According to the results of the research, it was determined that organizational trust has a negative and meaningful effect on the intention to leave the job, while it has a negative and meaningful effect on mushroom management. In addition, it has been determined that mushroom management has an mediation role in the relationship between organizational trust and the intention to leave the business. Conclusion: The perception of mushroom management, which is new in the literature, is important in order to examine and understand the subject holistically, in different samples and cultures, in institutions, as well as with different theories such as personality traits and leadership types.